Design and Development of a 1-Degree-of-Freedom Leg Exoskeleton for Rehabilitation - Shen, Zefang (Curtin University, 2019)
Current leg exoskeletons for rehabilitation are mostly heavy and bulky, which limits their applications in clinical settings. Moreover, portable leg exoskeletons driven by built-in batteries have limited working hours due to low energy efficiency. This thesis was aimed to develop a compact and portable leg exoskeleton with a long lasting battery life. The exoskeleton adopted a planar 1-DOF linkage for compactness and clutched-spring mechanisms for energy efficiency.